A construção de um taumaturgo: a prática missionária de Frei Damião de Bozzano no nordeste brasileiro (1931 - 1997). - Silva, Aerton Alexander de Carvalho (2019)
This thesis seeks to identify, from the devotees of Frei Damião de Bozzano, records and memories that structure the narratives, which lead them to recognize him as a holy thaumaturge. From 1931 to 1997, the period of his life and mission in Brazil, models of tridentine religion, popular catholicism and the emergence of post-conciliar times stood out. Also, society underwent significant changes in that period. In this scenario, we try to understand the variables that led the pilgrims to elect Frei Damião as counselor and confessor, godfather and thaumaturge. Having as theoretical reference the School of the Analles with its conceptions of history and memory of short, medium and long duration, deepened by Marc Bloch, Jaques Le Goff and Lucien Febvre. In addition to bibliographical research, semi-structured interviews with clerics and pilgrims were conducted. Therefore, it is possible to recognize that the northeastern people, with all their cultural wealth and especially their religiosity, built from the indigenous, catholic and african cultural matrices, are characterized as a fertile environment for construction of religious sceneries. Belonging to the traditional Order of Capuchin Friars Minor, which, since the colonial period, through a proper methodology, a significant role in the formation of the people and a decisive role in their religiosity, were recognized as men of faith, Frei Damião was heir of this symbolic capital that authorized him to exercise the role of mystic, confessor and counselor. In this sense, the counselors who preceded him, marked out the way for his person. He was recognized as a saint by the people. As in the case of the thaumaturgos kings of the middle ages, a tradition of the healing touch was developed around him. Crowds came to the places where the friar was, to hear his counsel, to confess the sins and to touch his body, bent over by time. Sustained by several senses underlying the needs of the people, the memories of long duration, the religiosity of the the people from de backwood, the thaumaturgy of Frei Damião was affirmed. After his death, devotion multiplied. Several sanctuaries were erected around their statues and relics. Thousands of people continue to nourish their faith, from devotion to the religious, to whom they call the Saint of the Northeast.